Quasi‐Hodgkin–Huxley Neurons with Leaky Integrate‐and‐Fire Functions Physically Realized with Memristive Devices - Huang, He‐Ming; Yang, Rui; Tan, Zheng‐Hua; He, Hui‐Kai; Zhou, Wen; Xiong, Jue; Guo, Xin (Advanced materials (Weinheim), 2019)
Artificial neurons with functions such as leaky integrate‐and‐fire (LIF) and spike output are essential for brain‐inspired computation with high efficiency. However, previously implemented artificial neurons, e.g., Hodgkin–Huxley (HH) neurons, integrate‐and‐fire (IF) neurons, and LIF neurons, only achieve partial functionality of a biological neuron. In this work, quasi‐HH neurons with leaky integrate‐and‐fire functions are physically demonstrated with a volatile memristive device, W/WO3/poly(3,4‐ethylenedioxythiophene): polystyrene sulfonate/Pt. The resistive switching behavior of the device can be attributed to the migration of protons, unlike the migration of oxygen ions normally involved in oxide‐based memristors. With multifunctions similar to their biological counterparts, quasi‐HH neurons are advantageous over the reported HH and LIF neurons, demonstrating their potential for neuromorphic computing applications. Quasi‐Hodgkin–Huxley (HH) neurons with leaky integrate‐and‐fire functions are physically demonstrated by W/WO3/poly(3,4‐ethylenedioxythiophene):polystyrene sulfonate/Pt memristive devices with a battery effect; in the device, proton migration plays a key role. With the help of a neuromorphic circuit, the neuron successfully emulates the multifunction of a biological neuron, being advantageous over previously reported HH and leaky integrate‐and‐fire neurons.